Needs Analysis of Innovative Visual Learning Media for Special School Teachers in Mathematics Learning for Deaf Students - Yustinizar Kusumaningtyas (Journal of Disability, 2021)
The purpose of the study was to determine the need for media, especially innovative visual media in learning mathematics for deaf students in Surakarta. The method used in this study was qualitative and quantitative. The subjects of this study were 35 teachers from several special schools in Central Java. The data collection technique using a questionnaire with a Likert scale refers to the aspects of the need for mathematics learning media, namely the interesting media aspect, the media convenience aspect and the media suitability aspect. The data analysis technique used a descriptive analysis approach. The results obtained an average of 3.27 (very high) for the attractive media aspect, 3.33 (very high) for the ease of media aspect and 3.31 (very high) for the media suitability aspect. Towards innovative visual media is included in the very high category.